Crane design using product family approach - Selvaganapati Karthick (2017)
The sector of construction is going through a phase of continuous improvement and finding a solution for complex problems. Starting from a basic material used for construction of building to the technology of advanced lifting systems for the efficient handling of building material, everywhere the improvement is evident. The crawler cranes are employed in construction sites relatively in less numbers when compared to tower cranes. But these cranes serve for greater purposes as they can move around the construction site to handle the loads at different locations. Thus crawler cranes can be used as a machine that can provide multi-location load lifting applications. This project aims to design and simulate different crawler crane models having a range of capabilities which is built through the computer software like Autodesk Inventor, Autodesk 3DS Max etc. The crane in general consists of enormous quantity of sub-parts and components that needs to be assembled in order to build an entire crane structure. For an Original Equipment Manufacturer (OEM), handling large number of distinctive parts for under each configuration of the crane is really a tedious job. So in order to simplify these difficulties the concept of Product Family approach is evolved. The Product family focuses on increasing the part commonality thus generating the modular components that fits across different families of cranes. The crawler crane models are designed by using product family approach having similarities of one or more components used across different variants of the cranes. Finally, the crawler crane models designed with product family approach is tested using the Graphics Processing Unit (GPU) based crane simulator software. Using this software, the crane models are simulated in the virtual industrial site. The lifting plan and position manipulation for the load is established. This lifting plan is generated with continuous monitoring on collision detection program that provides the safe trajectory to be followed during the material handling process.